The Influence of Economic Literacy, Financial Efficacy, and Decision Making Factors on Economic Rationality - Elpisah; Suarlin; Muhammad Hasan; Amir Pada; Muh Yahya (Migration Letters, 2023)
This research aims to analyze the economic rationality of economics students, which is influenced by economic literacy, financial efficacy, and decision-making factors. Using a quantitative type of research, this research uses a questionnaire as a data collection method. The population of this study was economic education students at Makassar State University, and the sample consisted of 187 students who answered the survey. This study analyzes the data using Structural Equation Modeling (SEM) analysis. Based on the findings, it is shown that the tests given to students on the three variables, namely (1) economic literacy (X1), have a significant effect on the economic rationality of Makassar State University economic education students (Y), (2) financial efficacy (X2) have a significant effect on the economic rationality of economic education students at Makassar State University (Y), and (3) has a significant effect on the economic rationality of economic education students at Makassar State University (Y). Meanwhile, the economic rationality of economic education students at Makassar State University has a significant effect on financial efficacy (X2), the decision factor decision (X3), and economic literacy (X1) variables, according to the partial significance test (Y).